Non‐conventional dysplasias of the tubular gut: a review and illustration of their histomorphological spectrum. Issue 5 (24th January 2021) - Pereira, Daniela; Kővári, Bence; Brown, Ian; Chaves, Paula; Choi, Won‐Tak; Clauditz, Till; Ghayouri, Masoumeh; Jiang, Kun; Miller, Gregory C; Nakanishi, Yukihiro; Kim, Kyoung M; Kim, Baek H; et al.
Abstract : The increasing use of gastrointestinal endoscopic procedures has led to the recognition by histopathologists of non‐conventional (or special‐type) dysplasias of the gastrointestinal tract. These lesions can be recognised in association with prevalent underlying gastrointestinal conditions, such as Barrett oesophagus, chronic atrophic gastritis, and inflammatory bowel disease. The diagnosis of these special types can be challenging, and their biological behaviours are not fully characterised. The aim of this review is to provide a global view of non‐conventional dysplastic lesions observed in the various segments of the tubular gastrointestinal tract and describe their salient features. Furthermore, as the clinical implications of these various subtypes have not been broadly tested in practice and are not represented in most management guidelines, we offer guidance on the best management practices for these lesions. Abstract :